2013
DOI: 10.1371/journal.pone.0075501
|View full text |Cite|
|
Sign up to set email alerts
|

Bions: A Family of Biomimetic Mineralo-Organic Complexes Derived from Biological Fluids

Abstract: Mineralo-organic nanoparticles form spontaneously in human body fluids when the concentrations of calcium and phosphate ions exceed saturation. We have shown previously that these mineralo-organic nanoparticles possess biomimetic properties and can reproduce the whole phenomenology of the so-called nanobacteria—mineralized entities initially described as the smallest microorganisms on earth. Here, we examine the possibility that various charged elements and ions may form mineral nanoparticles with similar prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
47
1
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 135 publications
(264 reference statements)
6
47
1
16
Order By: Relevance
“…But are they alive? The group around Martel and Young [22] [23] [26] claims that nanobacteria are only complex inorganic (mostly calcium carbonate or phosphate based)-organic (mostly protein) systems. These researchers managed to form nanobacteria like vesicles, called bions, on the basis of other cations than Ca, like Mn, Cu, Fe, Ni, Sr, Na etc.…”
Section: Nanobacteria and Their Biological Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…But are they alive? The group around Martel and Young [22] [23] [26] claims that nanobacteria are only complex inorganic (mostly calcium carbonate or phosphate based)-organic (mostly protein) systems. These researchers managed to form nanobacteria like vesicles, called bions, on the basis of other cations than Ca, like Mn, Cu, Fe, Ni, Sr, Na etc.…”
Section: Nanobacteria and Their Biological Statusmentioning
confidence: 99%
“…These researchers managed to form nanobacteria like vesicles, called bions, on the basis of other cations than Ca, like Mn, Cu, Fe, Ni, Sr, Na etc. (see [26]), but still with animal proteins, e.g. fetal bovine serum.…”
Section: Nanobacteria and Their Biological Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently demonstrated that mineralizing nanoparticles (NPs) form spontaneously in body fluids [1][2][3][4][5][6][7][8][9][10][11][12][13]. These calcium apatite NPs have further been shown to grow in size [8,10,11], seed new particles [2,3,11] and undergo amorphous to crystalline transformation [2,4,6], under which conditions they may resemble biomimetically submicroscopic lifeforms like bacteria [5,9,13].…”
mentioning
confidence: 99%
“…17 Also, if both types of particles, either calcifying microvesicles or calcifying nanoparticles, are present in the same plaque, they must somehow be biologically distinct from each other, or be calcifying microvesicles, another analogous substructure of calcifying nanoparticles? However, development of specific biomolecular markers against all biologically existing particles, including recently added bions, 18 holds the promise of putting an end to all ambiguities pertaining to their identities.…”
mentioning
confidence: 99%